Advanced m-CHP fuel cell system based on a novel bio-ethanol fluidized bed membrane reformer. (11th May 2017) - Viviente, Jose Luis; Meléndez, Jon; Pacheco Tanaka, David Alfredo; Gallucci, Fausto; Spallina, Vincenzo; Manzolini, Giampaolo; Foresti, Stefano; Palma, Vincenzo; Ruocco, Concetta; Roses, Leonardo
Abstract: Distributed power generation via Micro Combined Heat and Power (m-CHP) systems, has been proven to over-come disadvantages of centralized generation since it can give savings in terms of Primary Energy consumption and energy costs. The FluidCELL FCH JU/FP7 project aims at providing the Proof of Concept of an advanced high performance, cost effective bio-ethanol m-CHP cogeneration Fuel Cell system for decentralized off-grid applications by end of 2017. The main idea of FluidCELL is to develop a new bio-ethanol membrane reformer for pure hydrogen production (3.2 Nm 3 /h) based on Membrane Reactors in order to intensify the process of hydrogen production through the integration of reforming and purification in one single unit. The novel reactor could be more efficient than the state-of-the-art technology due to an optimal design aimed at circumventing mass and heat transfer resistances. Moreover, the design and optimization of the subcomponents for the BoP could also be improved. Particular attention has to be devoted to the optimized thermal integration that can improve the overall efficiency of the system at >90% and reducing the cost due to low temperature reforming. The main results obtained until now in terms of performance of the catalysts, membranes and the membrane reactors will be presented in this work. Highlights: Bimetallic catalyst for bioethanol reforming under fluidization at medium temperatures (500 °C). Scale-up of thin Pd-based membrane manufacturing. Long-term stability of thin Pd-based supported membranes. Performance of fluidized bed membrane reactors including thin Pd-based supported membranes. Design of PEM m-CHP system including membrane reactor.